Perspectives of the study of fission fragments structure on the Bremsstrahlung beams in project DRIBs (Dubna) - Yu.P, Gangrsky; D.V, Karaivanov; K.P, Marinova; B.N, Markov; I.M, Melnikova; G.V, Mishinsky; Yu.E, Penionzhkevich; S.G, Zemlyanoi; V.I, Zhemenik (Scientific transaction of the National University of Mongolia. Physics, 2022)
Fission fragments of heavy nuclei (Z > 90) are neutron-rich isotopes of the elements from Zn (Z = 30) to Nd (Z = 60) with a neutron number of 45 - 90. The large neutron excess in the fission fragments under study (in some cases there are 10 - 15 more neutrons, than in the nuclei situated in the -β stability valley) could lead to an essential change in their structure and radioactive decay characteristics.